Key signature genes of early terminal granulocytic differentiation distinguish sepsis from SIRS on ICU admission - Lindner, Holger A. (Universität, 2022)
Background: Infection can induce granulopoiesis. This process potentially gives rise to blood gene classifiers of sepsis in systemic inflammatory r...
Gesehen am 12.07.2022
Keywords: Forschungsdaten; Datenbank